2019
DOI: 10.1111/apm.12919
|View full text |Cite
|
Sign up to set email alerts
|

The role of Tenascin‐C and Twist1 in gastric cancer: cancer progression and prognosis

Abstract: The aim of the present study was to identify the relation between Tenascin‐C (TNC) and Twist1 and determine their clinical significance in gastric cancer (GC). We analyzed the expression of TNC and Twist1 in 159 GC samples and in 91 non‐tumor samples using immunohistochemistry. In this study, TNC expression in stromal fibroblasts of GC was remarkably higher than non‐tumor gastric lesions. The expression of TNC in GC stromal fibroblasts was significantly associated with pT stage, lymph node metastasis, distant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 19 publications
3
9
0
Order By: Relevance
“…Recent studies demonstrated that TNC was strongly expressed and indicated poor prognosis in gastric cancer [16,20]. The present results con rmed that TNC was upregulated in gastric cancer tissues and patients with higher TNC levels had signi cantly shorter overall survival (OS) and relapse free survival (RFS) compared to those with low TNC expression, consistent with our single-center data.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Recent studies demonstrated that TNC was strongly expressed and indicated poor prognosis in gastric cancer [16,20]. The present results con rmed that TNC was upregulated in gastric cancer tissues and patients with higher TNC levels had signi cantly shorter overall survival (OS) and relapse free survival (RFS) compared to those with low TNC expression, consistent with our single-center data.…”
Section: Discussionsupporting
confidence: 90%
“…However, it is speci cally upregulated during wound healing, chronic in ammation or cancer [19]. Recent studies have shown that the expression of TNC was signi cantly associated with pT stage, lymph node metastasis and distant metastasis in gastric cancer [20]. TNC was identi ed in inducing epithelial-to-mesenchymal (EMT) transition [21] and EMT has been found to play a key role in VM formation [9,22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Several genes belonging to those pathways were overexpressed in DUSP6 depleted cells. One of them, Tenascin-C expression is upregulated and has been involved in gastric [15] and gastric GIST cancer progression [16], increased proliferation in pancreatic cancer [17] and is a prognostic determinant of colorectal cancer through induction of epithelial to mesenchymal transition and proliferation [18]. CCND2 gene has been shown to be targeted by expression of mir-4317 and miR-671-3p and related to inhibition of cancer progression in NSCLC [19].…”
Section: Discussionmentioning
confidence: 99%
“…TNC in eCCA has not been reported. However, TNC presence in gastrointestinal malignancies such as pancreatic ductal [ 78 , 79 ], oesophageal [ 80 ], gastric [ 81 ], and colorectal [ 82 ] adenocarcinoma have been described.…”
Section: Discussionmentioning
confidence: 99%